Development of teaching materials based on realistic mathematics education to facilitate students’ mathematical critical thinking skills - Zameza, Ranty Andika Abinaya; Maimunah; Hutapea, Nahor Murani (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study aims to develop mathematics teaching material based on the Realistic Mathematics Education (RME) approach that is valid and practical to facilitate the mathematical critical thinking skills of eighth-grade junior high school students. The research was motivated by the low level of students’ critical thinking skills and the lack of teaching materials that support their development. This research employed a development method using the 4D model, which includes the stages of define, design, develop, and disseminate. The limited trial involved 17 eighth-grade students at SMP Negeri 2 in the Suliki subdistrict. The instruments used included expert validation sheets and student response questionnaires. The results showed that the teaching material obtained a validity score of 85.05% (valid category) and a practicality score of 87.38% (very practical category). Analysis of students’ written work also showed that the material effectively facilitated critical thinking indicators such as interpretation, analysis, and inference. Therefore, the developed teaching material is recommended for use in mathematics instruction for eighth-grade students.